2012
DOI: 10.1016/j.exer.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A Class I UV-blocking (senofilcon A) soft contact lens prevents UVA-induced yellow fluorescence and NADH loss in the rabbit lens nucleus in vivo

Abstract: It is known that fluorescence, much of it caused by UVA light excitation, increases in the aging human lens, resulting in loss of sharp vision. This study used an in vivo animal model to investigate UVA-excited fluorescence in the rabbit lens, which contains a high level of the UVA chromophore NADH, existing both free and bound to λ-crystallin. Also, the ability of a Class I (senofilcon A) soft contact lens to protect against UVA-induced effects on the rabbit lens was tested. Rabbit eyes were irradiated with U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…The expression of Bcl-2 has also been demonstrated in primary lens fibers. Expression has not been detected in the epithelial cells at the center of the anterior envelope of the crystalline lens; however, transcription has been shown to initiate when these cells move to the equator (15,16). The specificity of tissue localization indicates that Bcl-2 is transcribed and expressed (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Bcl-2 has also been demonstrated in primary lens fibers. Expression has not been detected in the epithelial cells at the center of the anterior envelope of the crystalline lens; however, transcription has been shown to initiate when these cells move to the equator (15,16). The specificity of tissue localization indicates that Bcl-2 is transcribed and expressed (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Further in vivo work by Giblin et al . found that UVA and UVB blocking contact lenses prevented UVR‐induced cataract in rabbits.…”
Section: Introductionmentioning
confidence: 94%
“…Other work has found that light scattering develops in guinea pig lens after UVA exposure in vivo in the laboratory (34). Further in vivo work by Giblin et al (35,36) found that UVA and UVB blocking contact lenses prevented UVR-induced cataract in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Eyes of anesthetized rabbits were exposed to UVR radiation using a Desaga MinUvis Hg (Sarstedt AG & Co., Nümbrecht, Germany) with the following properties: one low-pressure lamp at 254 nm 1.0 mW/cm 2 and one low-pressure lamp at 366 nm, 1.2 mW/cm 2 ). A distance of 7 cm from the cornea was chosen, according to the procedure described by Giblin et al (2012). The rabbits of IG, G30 and G60 were undergone to the radiation (100 mW/cm 2 ) for 30 and 60 min.…”
Section: Uvr Radiationmentioning
confidence: 99%